PENGARUH UKURAN PERUSAHAAN DAN KEPEMILIKAN INSTITUSIONAL TERHADAP AGRESIVITAS PAJAK DENGAN CORPORATE SOCIAL RESPONSIBILITY (CSR) SEBAGAI VARIABEL MODERASI (Studi Empiris Pada Perusahaan Manufaktur) - sunarti, sunarti sunarti (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2019)
This study aims to examine and determine whether Corporate Social Responsibility (CSR) can weaken and strengthen the relationship between firm size and institutional ownership of tax aggressiveness. The information in the annual reports or corporate finances used to test and quantify the proxies of those variables. The population used is manufacturing firm listed on the Indonesia Stock Exchange (IDX) in 2018, where 61 firms were selected as research samples. Data were analyzed using SPSS 25 with Moderated Regression Analysis (MRA). The results showed that firm size and institutional ownership not have effect on tax aggressiveness. Corporate Social Responsibility (CSR) can not weaken the relationship of firm size to tax aggressiveness and CSR can not also strengthen the relationship of institutional ownership to tax aggressiveness.Keywords: Corporate Social Responsibility (CSR), Firm Size, Institutional Ownership, and tax Aggressivness.